Internalization of Islamic Living Values in the Formation of Self-Regulation of the Temboro Community - Nayla Nur Rahmawati; Aqilla Tarishoh Putri; Sarah Sakhowah; Rafi Ahlina Majid; Andre Prayoga Mardian; Dhika Bintang Dwiputra; Wirya Fatiha Alif; Andy Hadiyanto (IQRO: Journal of Islamic Education, 2026)
This study aims to identify the forms of Living Islam practices, analyze the internalization process of these values, and explore their impact on the self-regulation of the Temboro community. The phenomena of moral disorientation and self-control crisis in the modern era necessitate an alternative spiritual-based behavioral control model. This research employs a qualitative descriptive method with data collection through interviews, observation, and documentation involving civil society around the Al-Fatah Islamic Boarding School, Temboro. The results indicate that Living Islam in Temboro manifests in an Islamic dress code, collective worship routines, and daily spiritual habits. The internalization process occurs through the integration of the social-religious ecosystem, which successfully transcends pesantren boundaries into civil society. Ultimately, this practice significantly impacts community self-regulation (mujahadah an-nafs), demonstrated by autonomous obedience to religious ethics without legal coercion. These findings offer a community-based self-regulation model rooted in a living socio-religious ecosystem. The implications of this study emphasize the necessity of structuring socio-religious ecosystems and environmental role modeling in character building, rather than relying solely on normative classroom instruction. Practically, this model provides a framework for educational institutions and policymakers to design community-based character development programs. For future research, it is recommended to examine the resilience of personal self-regulation when individuals interact outside the Temboro ecosystem and to conduct comparative studies across different pesantren environments.